KAJIAN ETNOPEDAGOGIK ADAT PERPANDAYAN DI DESA TARAJU KECAMATAN SINDANGAGUNG KABUPATÉN KUNINGAN SEBAGAI BAHAN PEMBELAJARAN MEMBACA BERBASIS KEARIFAN LOKAL - Heti Triwahyuni; Leni Nuraeni; Mimin Suminar Suminar (Prodi Pendidikan Bahasa dan Sastra Daerah, 2021)
Mimin Suminar (165223012), Ulikan Étnopédagogik Customary Perpandayan Taraju Village Sindangagung District Kabupatén Kuningan Pikeun Pangahasa Maca Based on Local Wisdom. The Study Program for Language and Literature in Regional Education (PBSD) 2020, pages. This research has a very broad background, one of which is the lack of knowledge of the people of Taraju Village about Indigenous culture of rejuvenation. The purpose of this study are: (1) describing ethnopegagogic studies in the custom of Reward Ceremony in Taraju Village Sindangagung Subdistrict Kuningan Regency (2) describing the Customary Cultural Elements of the Rewahan Reward in Taraju Village Sindangagung Subdistrict Kuningan Regency (3) describing how Alternative Pangaca Alternative is based on Kuningan Local culture. The traditional rewards of Perpandayan are carried out by the people of the village of Taraju who have a goal of preserving Sundanese culture and hoping that their culture is maintained and carried out every year. The method used in this study is a qualitative method by organizing data, describing data, arranging patterns, choosing important things, and making conclusions in the order of customary rewards in the village of Taraju, Sindangagung District, Kuningan Regency. With the technique of collecting data through observation, interviews and documentation. The results of this study are the ethnopedagogic studies in the traditional rewards of bathing in the village of Taraju consisting of 4 ethnopedagogic studies including 4 human identity chess, 6 human morals, 5 pancawaluya gates and 3 Tri-silas delay behavior. Cultural elements in the traditional rewards of culture in the village of Taraju consist of 7 cultural elements. Alternative learning of Sundanese bases in the form of Articles. Keywords: Ethnopedagogic study, reading learning, Taraju village guide